Risk factors for diabetes mellitus after acute pancreatitis: a systematic review and meta-analysis - Zahariev, Olga Julia; Bunduc, Stefania; Kovács, Adrienn; Demeter, Dóra; Havelda, Luca; Budai, Bettina Csilla; Veres, Dániel Sándor; Hosszúfalusi, Nóra; Erőss, Bálint Mihály; Teutsch, Brigitta; Juhász, Márk Félix; Hegyi, Péter (Frontiers in Medicine, 2024)
Introduction: Within five years of having acute pancreatitis (AP), approximately 20% of patients develop diabetes mellitus (DM), which later increases to around 40%. Some studies suggest that the prevalence of prediabetes (PD) and/or DM can grow as high as 59% over time. However, information on risk factors is limited. We aimed to identify risk factors for developing PD or DM following AP. Methods: We systematically searched three databases up to 2023.09.04 extracting direct, within-study comparisons of risk factors on the rate of new-onset PD and DM in AP patients. When PD and DM event rates could not be separated, we reported results for this composite outcome as PD/DM. Meta-analysis was performed using the random-effects model to calculate pooled odds ratios (OR) with 95% confidence intervals (CI). Results: Of the 61 studies identified, 50 were included in the meta-analysis, covering 76,797 participants. The studies reported on 79 risk factors and meta-analysis was feasible for 34 risk factor and outcome pairs. The odds of developing PD/DM was significantly higher after severe and moderately severe AP (OR: 4.32; CI: 1.76-10.60) than mild AP. Hypertriglyceridemic AP etiology (OR: 3.27; CI: 0.17-63.91) and pancreatic necrosis (OR: 5.53; CI: 1.59-19.21) were associated with a higher risk of developing PD/DM. Alcoholic AP etiology (OR: 1.82; CI: 1.09-3.04), organ failure (OR: 3.19; CI: 0.55-18.64), recurrent AP (OR: 1.89; CI: 0.95-3.77), obesity (OR: 1.85; CI: 1.43-2.38), chronic kidney disease (OR: 2.10; CI: 1.85-2.38), liver cirrhosis (OR: 2.48; CI: 0.18-34.25) and dyslipidemia (OR: 1.82; CI: 0.68-4.84) were associated with a higher risk of developing DM. Discussion: Severe and moderately severe AP, alcoholic and hypertriglyceridemic etiologies, pancreatic necrosis, organ failure, RAP and comorbidities of obesity, chronic kidney disease liver disease and dyslipidemia are associated with a higher risk of developing PD or DM.